The Effectiveness of the Means-Ends Analysis Learning Model with a Realistic Approach toward Mathematical Creative Thinking Ability in terms of Self -Regulated Learning - Novegitasari, Yenatin; Dwijanto, Dwijanto; Asih, Tri Sri Noor (FKIP Universitas Lampung, 2023)
This research is a quantitative research, the purpose of this research is to determine the effectiveness of the MEA learning model with a realistic approach to students' mathematical creative thinking abilities in terms of self-regulated learning. This type of research is True Experimental with Pretest Posttest Control Group Design. Data collection techniques used in this study were tests of mathematical creative thinking skills, self-learning questionnaires, and documentation. From this study it can be concluded that the learning model means ends analysis with a realistic approach is effective for mathematical creative thinking abilities.Keywords: mathematical creative thinking ability, Means-Ends Analysis, realistic approach, self -regulated learningDOI: http://dx.doi.org/10.23960/jpmipa/v24i1.pp183-190